Microplastic and POP contamination in rural waste-dumping sites, India - Gautam, Sneha; Rakshith, Bairi Levi; Asirvatham, Lazarus Godson; Haokip, Joseph Mangkhohao; Kumar, Aman; Khongsai, Letgoulen; Khongsai, Letminlen; Ho, Chang-Hoi (Frontiers in Environmental Science, 2025)
Persistent organic pollutants (POPs) are highly toxic and long-lived environmental contaminants that easily adsorb onto the surfaces of microplastics (MPs). While urban and industrial environments have been extensively studied, rural areas, especially in developing countries, have received limited attention. In such regions, uncontrolled waste dumping exacerbates the contamination of water and soil systems by MPs and associated POPs, causing significant environmental and health concerns. This study quantified MP pollution in soil and water near unregulated waste‐dumping sites in Tamil Nadu, India. A total of 20 environmental samples (10 soil and 10 water) were collected from two active rural dump sites. MPs were extracted using density separation and characterized by stereomicroscopy and Fourier transform infrared spectroscopy. MPs were detected in all samples, with polypropylene (PP) and polyethylene (PE) identified as the dominant polymer types. Soil samples contained 49.87% PP and 21.62% polyethylene terephthalate, while water samples comprised 57.14% PP and 28.57% PE. These polymers were particularly effective at adsorbing and transporting POPs through environmental media. The presence of MPs and POPs in drinking water sources and agricultural soils poses a significant threat to the ecological integrity of these rural areas and the health of their communities. The present results underscore the urgent need for enhanced waste management practices and robust water protection policies to mitigate the long-term health impacts and environmental degradation in these regions.